The Importance of The Code of Ethics in The Public Accountant Profession - Lailatul Nafiisa, Birra; Ekasari, Kurnia; Dewi Sri Susilowati, Kartika (Journal of Applied Business, Taxation and Economics Research, 2023)
This study aims to provide an overview and analyze the code of ethics for the public accounting profession and is expected to be used as reference material in terms of the practical application of the code of ethics in Indonesia. This type of research is descriptive qualitative. The data collection method in this qualitative research uses secondary data from scientific journals and books from other parties that support researchers in completing research data. The findings of this research can be used to develop new policies or improve tighter oversight measures for public accountants. This will help improve the quality of accounting practices, restore public trust, and maintain the integrity of the public accounting profession in Indonesia. The results of this study are important for the public accounting profession to uphold a code of ethics such as: integrity, objectivity, prudence, confidentiality, and professionalism in order to maintain public trust in entity financial information, ensure fairness in financial reporting, and provide quality audit services. In addition, this also has a positive impact on the reputation of the public accounting profession as a whole.